The effect of exercise on inflammatory biomarkers - Moore, Samantha J. (2020)
Introduction Many non-communicable diseases (NCDs) including dementia and some cancers have a component of underlying inflammation within their pathophysiology. Exercise has been shown to reduce morbidity and mortality from NCDs and has been linked with decreased levels of pro-inflammatory cytokines in the plasma of regularly exercising individuals. This project seeks to assess the effect of acute and chronic exercise, including high intensity interval training on inflammatory markers within the cerebrospinal fluid (CSF) and plasma.